Measuring Critical Thinking within Discussion Forums using a Computerised Content Analysis Tool - Corich, Stephen; Kinshuk; Hunt, Lynn M. (Proceedings of the International Conference on Networked Learning, 2006)
The use of discussion forums as a means of promoting collaboration and interaction between distance education students is increasing as a result of the growing popularity of online learning. The transcripts of these discussion forums have provided researchers an opportunity to analyse the interactions between participants and investigate evidence of cognitive and metacognitive activity. This paper outlines some of the methodologies adopted by researchers who have attempted to measure evidence of cognitive processes and critical thinking among discussion forum participants. It also investigates the use of computers in the content analysis process and describes the use of automated tools to analyse discussion forum transcripts. The paper then introduces a computerised tool, which has been designed with the aim of allowing different content analysis methodologies to be compared. The paper describes how the tool was used to analyse the discussion forum transcripts from a first year undergraduate degree course and discusses how the results obtained using the tool compared to a manually coded set of results.